Smart Energy Meter for Computing Energy Cost Based on Consumers Category and Tariff Rates - R, Jaichandran; S, Rajaprakash; Kumar Verma, Amit; Sinha, Abhishek; Kumar Singh, Pankaj (International Journal of Engineering and Technology, 2018)
This paper present a smart energy meter for computing energy cost based on consumers category and tariff rates. Proposed smart energy meter computes consumer energy cost, subsidy amount, and payable energy cost based on consumers category and tariff rates of Tamil Nadu electricity board. Prototype is experimented in various scenarios and evaluated using test cases. Results show the proposed smart energy meter is effective in computing energy cost based on consumers category and tariff rates.Â